Cryo-EM of elongating ribosome with EF-Tu•GTP elucidates tRNA proofreading - Loveland, Anna B; Demo, Gabriel; Korostelev, Andrei A (Nature, 2020)
Ribosomes accurately decode mRNA by proofreading each aminoacyl-tRNA that is delivered by the elongation factor EF-Tu1. To understand the molecular mechanism of this proofreading step it is necessary to visualize GTP-catalysed elongation, which has remained a challenge2-4. Here we use time-resolved cryogenic electron microscopy to reveal 33 ribosomal states after the delivery of aminoacyl-tRNA by EF-Tu•GTP. Instead of locking cognate tRNA upon initial recognition, the ribosomal decoding centre dynamically monitors codon-anticodon interactions before and after GTP hydrolysis. GTP hydrolysis enables the GTPase domain of EF-Tu to extend away, releasing EF-Tu from tRNA. The 30S subunit then locks cognate tRNA in the decoding centre and rotates, enabling the tRNA to bypass 50S protrusions during accommodation into the peptidyl transferase centre. By contrast, the decoding centre fails to lock near-cognate tRNA, enabling the dissociation of near-cognate tRNA both during initial selection (before GTP hydrolysis) and proofreading (after GTP hydrolysis). These findings reveal structural similarity between ribosomes in initial selection states5,6 and in proofreading states, which together govern the efficient rejection of incorrect tRNA.
Keywords: Peptide Elongation Factor Tu; Models, Molecular; Hydrolysis; guanosintrifosfát; guanosindifosfát; messenger RNA; RNA, Transfer; Guanosine Triphosphate; hydrolýza; ribozomy; Rotation; Escherichia coli; molekulární modely; Ribosomes; RNA transferová; RNA, Messenger; Guanosine Diphosphate; GTP-fosfohydrolasy; elongační faktor Tu; rotace; elektronová kryomikroskopie; Cryoelectron Microscopy; GTP Phosphohydrolases